2015
DOI: 10.1097/yct.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol, Etomidate, and Thiopental in Anesthesia for Electroconvulsive Therapy

Abstract: Propofol, etomidate, and thiopental are associated with similar safety and efficacy profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 0 publications
3
19
0
1
Order By: Relevance
“…in which mean motor seizure duration was significantly longer in etomidate as compared to propofol group ( P < 0.05). [ 10 11 ] Our results are also similar to a study done by Gazdag et al . in which propofol (1 mg.kg −1 ) and etomidate (0.2 mg.kg −1 ) were compared during the ECT of patients with schizophrenia based on their impact on seizure activity and seizure-induced hemodynamic reactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…in which mean motor seizure duration was significantly longer in etomidate as compared to propofol group ( P < 0.05). [ 10 11 ] Our results are also similar to a study done by Gazdag et al . in which propofol (1 mg.kg −1 ) and etomidate (0.2 mg.kg −1 ) were compared during the ECT of patients with schizophrenia based on their impact on seizure activity and seizure-induced hemodynamic reactions.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the meantime to spontaneous respiration was shorter with propofol as compared to etomidate. [ 8 11 ] The propofol has an onset time of 40 s and also the metabolism of propofol is rapid which occurs mainly in the liver accounting for its rapid induction and recovery. [ 18 ] Avramov et al .…”
Section: Discussionmentioning
confidence: 99%
“…In some patients with high seizure threshold, etomidate is the firstline medication and it can improve the therapeutic effects of ECT sessions. [14] In the current study, seizure duration in ECT sessions in the etomidate group was longer than sodium thiopentone. Conca et al also observed similar findings with those in our study, in their study of 13 ECT patients.…”
Section: Discussionmentioning
confidence: 80%
“…In a study conducted at Bakirkoy Training and Research Hospital for Psychiatry, Neurology and Neurosurgery, we see that ECTs are most frequently used in the treatment of the manic phase of bipolar disorder patients (22). In another study conducted in the same hospital, 46.9% of the inpatients over a three-year period receiving ECT treatment were diagnosed with affective disorder and 52.1% suffered from psychotic disorder (25).…”
Section: Discussionmentioning
confidence: 99%